Chronic Tennis Elbow Treated by Platelet-Rich Plasma Versus Steroid Injections: A Comparative Study - Al-Edanni, Mohammed Sh. (AL-Kindy College Medical Journal, 2020)
Background: Painful elbow joint over the lateral epicondyle especially with resisted wrist extension are common signs of lateral epicondyle tendinopathy, also called tennis elbow. Objective: To evaluate the clinical outcome of local platelet rich plasma (PRP) injection in patients with chronic tennis elbow compared with a steroid (Depomedrol 40 mg) injection. Methods: A total of 88 patients with chronic tennis elbow were treated at Al-Kindy Teaching Hospital and private clinics. All patients had chronic pain for about 24 weeks or more and had failed first line treatment. The patients dividing into two groups, Group A injected with PRP (n = 44), and group B injected with depomedrol 40 mg (n = 44). A good clinical result was demarcated as 25% or more progress on the visual analog scale for pain. All patients followed for 6 months in both group for clinical successful result. Results: At three months (n = 44), in group A reported a perfection of 58.2% in their pain scores while 49.3% in the group B (N = 44). At 6 months follow up, the group A informed a perfection of 74.3% in their pain scores while 58.4 % in the group B. The local elbow tenderness recording at three months was 37.4% in the group A, while in the group B was 48.4%. At six months, 16.1% versus 30.2% recounted major elbow tenderness (P = .009) in groups (A and B) respectively. The clinical improvement rates at three months revealed no changes between both groups while it showed more significant clinically changes in group A ( 87.1%) than in group B (70.1 %) with P value = 0.008 after six months follow up. Conclusion: No important changes were found at 3 months in both groups, but at 6months, clinical significant perfections in patients treated with PRP group (group A)